2001
DOI: 10.1128/mcb.21.16.5471-5477.2001
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Hepatic Uptake and Intestinal Excretion of Organic Cations in Mice with a Targeted Disruption of the Organic Cation Transporter 1 (Oct1 [Slc22a1]) Gene

Abstract: The polyspecific organic cation transporter 1 (OCT1 [SLC22A1]) mediates facilitated transport of small (hydrophilic) organic cations. OCT1 is localized at the basolateral membrane of epithelial cells in the liver, kidney, and intestine and could therefore be involved in the elimination of endogenous amines and xenobiotics via these organs. To investigate the pharmacologic and physiologic role of this transport protein, we generated Oct1 knockout (Oct1 ؊/؊ ) mice. Oct1 ؊/؊ mice appeared to be viable, healthy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
161
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(172 citation statements)
references
References 28 publications
10
161
1
Order By: Relevance
“…Thus, shortly after iv administration [ 14 C]TEA plasma levels, i.e., plasma drug availability, may be higher in BDL than in sham-operated rats resulting in an initially more rapid clearance of TEA from plasma via the kidney, which is the main excretory route for small organic cations in contrast to biliary excretion, 33 which contributes only minimally to the overall clearance of TEA. 19 However, because we did not analyze [ 14 C]TEA levels in plasma or urine at earlier time points, this possibility remains speculative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, shortly after iv administration [ 14 C]TEA plasma levels, i.e., plasma drug availability, may be higher in BDL than in sham-operated rats resulting in an initially more rapid clearance of TEA from plasma via the kidney, which is the main excretory route for small organic cations in contrast to biliary excretion, 33 which contributes only minimally to the overall clearance of TEA. 19 However, because we did not analyze [ 14 C]TEA levels in plasma or urine at earlier time points, this possibility remains speculative.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with findings in Oct1 knockout mice where the hepatic accumulation of [ 14 C]TEA was only 23% of that in wild-type mice. 19 Because Oct1 is an electrogenic transporter, 2 changes in the membrane potential could theoretically also affect [ 14 C]TEA accumulation in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, transporters appear to play important roles in the absorption, distribution and elimination of metformin. Many studies have shown that metformin is a substrate of various polyspecific organic cation transporters, which are important determinants of pharmacokinetics, including OCT1 (SLC22A1), OCT2 (SLC22A2), OCT3 (SLC22A3), MATE1 (SLC47A1), MATE2 (SLC47A2), PMAT (SLC29A4), and OCTN1 (SLC22A4) [11][12][13][14][15][16] (Fig. 1.1, Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Because of its multispecificity for many xenobiotics and its abundant expression in the liver, it has been proposed that the primary role of OCT1 is to work in concert with drug-metabolizing enzymes (e.g., cytochrome P450s) in detoxification pathways in the liver (5). In fact, with the exception of changes in hepatic drug disposition, Oct1 knockout mice appear healthy with no obvious phenotypic abnormalities (3,6).…”
mentioning
confidence: 99%